Penggunaan Multimedia Interaktif Berbasis Bahasa Inggris untuk Meningkatkan Pemahaman Nilai-Nilai Islam Siswa - Khittotun Nahidin (PPPM STIT MIFTAHUL MIDAD, 2025)
In the context of Islamic higher education, fostering students’ moral development alongside academic competence presents a significant pedagogical challenge. This study explores the implementation of English-based interactive multimedia as an instructional strategy to enhance first-semester students’ understanding of Islamic values at STIT Miftahul Midad Lumajang. Employing a qualitative research approach, data were collected through classroom observations and semi-structured interviews with students and lecturers. The findings reveal that the integration of multimedia tools such as digital storytelling, animated videos, and interactive presentations not only increases student engagement but also facilitates deeper reflection on Islamic teachings. Additionally, the use of English as the medium of instruction supports language acquisition while contextualizing moral concepts. The study concludes that English-based interactive multimedia holds significant potential for developing culturally responsive and linguistically integrated moral education in Islamic academic settings. These findings provide useful insights for educators seeking to innovate value-based instruction through digital tools. Future research is encouraged to explore the long-term impact of such multimedia integration on students’ character formation and language development.